Effects of alkyl chain length of monomer and dye-doped type on the electro-optical properties of polymer-dispersed liquid crystal films prepared by nucleophile-initiated thiol-ene click reaction. Issue 5 (8th April 2020) - Zhang, Li; Liu, Yawen; Shi, Zhiqing; He, Taoyu; Gong, Xinjian; Geng, Pengfei; Gao, Zhenwei; Wang, Yinghan
ABSTRACT: Polymer-dispersed liquid crystal (PDLC) films containing a series of monomers with different alkyl chain lengths were prepared by nucleophile-initiated thiol-ene click reaction. The effect of alkyl chain length of monomers, dye and temperature on electro-optical properties of PDLC films was investigated. It was found that the alkyl chain length and polymerisation rate of monomers together determine the size of liquid crystal (LC) droplets, thus affecting the electro-optical properties of PDLC. In addition, the type and content of dyes could be optimised to obtain PDLC materials with better comprehensive properties for display. Graphical abstract: